2007
DOI: 10.1088/0957-4484/18/48/485302
|View full text |Cite
|
Sign up to set email alerts
|

A deep sub-wavelength process for the formation of highly uniform arrays of nanoholes and nanopillars

Abstract: We report a low-cost and high-throughput process for the realization of two-dimensional arrays of deep sub-wavelength features using silica and polystyrene spheres. The pattern size in this method is a weak function of sphere size, and hence excellent size uniformity is achievable. Also, the period and diameter of the holes and pillars formed with this technique can be controlled precisely and independently. Moreover, the patterns can be formed in conventional negative and positive photoresists, and hence this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
110
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 22 publications
0
110
0
1
Order By: Relevance
“…When the incident light is scattered by a homogenous single dielectric sphere, a tightly focused beam with a subwavelength waist emerges on the shadow side of the sphere. The nanojet has potential applications in nanoparticle sensing [2], subwavelength nanopatterning and nanolithography [3,4], and the realization of a low-loss coupled resonator optical waveguide [5,6]. For all applications, it is desired that the nanojets extend as far as possible in the forward direction.…”
mentioning
confidence: 99%
“…When the incident light is scattered by a homogenous single dielectric sphere, a tightly focused beam with a subwavelength waist emerges on the shadow side of the sphere. The nanojet has potential applications in nanoparticle sensing [2], subwavelength nanopatterning and nanolithography [3,4], and the realization of a low-loss coupled resonator optical waveguide [5,6]. For all applications, it is desired that the nanojets extend as far as possible in the forward direction.…”
mentioning
confidence: 99%
“…It has been demonstrated that microspheres on sample material can decrease the laser direct-etching, especially if the ultrafast (pico-or femto-seconds) lasers or shorter wavelength (ultra-violet range) lasers [7][8][9][10][11][12][13]. This decreasing size potency also has been demonstrated for nanosecond pulsed near-infrared lasers [14,15] that considered as more economical option than ultrafast pulsed ultra-violet lasers -not to mention its availability in well-packaged source.…”
Section: Introduction: Photonic Jet Etching Using Microspheresmentioning
confidence: 98%
“…Many people have already attempted applying the photonic jets for marking or surface patterning. However, most of them consider pico/femto-second or ultraviolet lasers [30][31][32][33][34][35][36][37][38][39].…”
mentioning
confidence: 99%
“…The photonic jets allow high concentration of light intensity with factor from 20 to more than 200 [29,32,33]. This factor can allow lower power laser, like nanosecond infrared lasers, to process materials with low absorbance.…”
mentioning
confidence: 99%